2011
DOI: 10.1590/s1807-59322011000200015
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular and open repair for blunt aortic injury, treated in one clinical institution in Brazil. A case series

Abstract: OBJECTIVE:The objective of this retrospective study is to analyze and compare the results of conventional surgical repair and endovascular treatment of blunt aortic injury over the past 8 years.METHODS:Twenty‐eight patients (25 male; mean age, 35 years) were treated for blunt aortic injury between April 2001 and March 2009 in a university hospital in Brazil. Twenty‐six patients were included in the study: five were treated with operative repair (OR) and 21 with endovascular treatment (TEVAR). Two patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Selection of appropriate surgical candidates may substantially improve survival rates among these patients. Sincos et al [20] retrospectively analyzed and compared the results of conventional surgical repair and endovascular treatment of blunt aortic injury in 26 patients treated for blunt aortic injury. Twenty-six patients were included in the study, 5 treated with operative repair and 21 with endovascular treatment and found that endovascular treatment was a safe method for repair of blunt aortic trauma, with immediate and midterm results that were comparable to those results obtained with operative repair.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%
“…Selection of appropriate surgical candidates may substantially improve survival rates among these patients. Sincos et al [20] retrospectively analyzed and compared the results of conventional surgical repair and endovascular treatment of blunt aortic injury in 26 patients treated for blunt aortic injury. Twenty-six patients were included in the study, 5 treated with operative repair and 21 with endovascular treatment and found that endovascular treatment was a safe method for repair of blunt aortic trauma, with immediate and midterm results that were comparable to those results obtained with operative repair.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%
“…Thoracic endovascular aortic repair (TEVAR) with stent-grafts has lower mortality and paraplegia rates than open surgery, but long-term results are still awaited. 47…”
mentioning
confidence: 99%
“…According to Sincos et al, (57) endovascular treatment is a safe method for repairing blunt aortic trauma, with immediate and mid-term results that were comparable to those obtained with surgical repair. No complications caused by the stent graft were identified during the follow-up period (mean, 33 months).…”
Section: Referencesmentioning
confidence: 95%